A case of 5-fluorouracil toxicity - C. Fucile; V. Marini; L. Robbiano; F. Mattioli; A. Martelli (Journal of Biological Research, 2011)
Dihydrouracil (UH2)/Uracil (U) ratio in plasma was determinated as a surrogate marker for dihydropyrimidine dehydrogenase (DPD) activity. The purpose of the study was to investigate the ralationship between the UH2/U plasma ratio and the variation of DPD gene (DPYD), associated with a deficiency of DPD activity, in a patient who developed a severe adverse reaction to 5-fluorouracil. Patient's plasma smaple and those of 20 healthy volunteers, used as control, were analyzed. The plasma concentrations of UH2 and U were assayed by HPLC-UV. UH2/U plasma ratio of the patient was 4.31; the mean ± SD of UH2/U plasma ratios in controls was 5.26 ± 2.08. The UH2/U ratio of the patient was lower than the mean values recorded from a reference population suggesting a reduction of DPD activity according to haplotype of the patient, previously identified.